If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(b + 6) + 6 = 30 + 4b Reorder the terms: 7(6 + b) + 6 = 30 + 4b (6 * 7 + b * 7) + 6 = 30 + 4b (42 + 7b) + 6 = 30 + 4b Reorder the terms: 42 + 6 + 7b = 30 + 4b Combine like terms: 42 + 6 = 48 48 + 7b = 30 + 4b Solving 48 + 7b = 30 + 4b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-4b' to each side of the equation. 48 + 7b + -4b = 30 + 4b + -4b Combine like terms: 7b + -4b = 3b 48 + 3b = 30 + 4b + -4b Combine like terms: 4b + -4b = 0 48 + 3b = 30 + 0 48 + 3b = 30 Add '-48' to each side of the equation. 48 + -48 + 3b = 30 + -48 Combine like terms: 48 + -48 = 0 0 + 3b = 30 + -48 3b = 30 + -48 Combine like terms: 30 + -48 = -18 3b = -18 Divide each side by '3'. b = -6 Simplifying b = -6
| (x/x-5)^-1 | | Y=51-3z | | -8(t+1)+2t=7+t | | y=x/(x-5) | | 27x^4-18x^3/(3x^2) | | 16=8/3x | | X=6y+28 | | 27x^4-18x^3/3x^2 | | x(x-4)=x^2+2x+5 | | 156/26=18/x | | 4m-15m^2=0 | | 5f-4=46 | | 2p+20=22 | | 15a^2+20a^3=0 | | 2X+3Y+9= | | z^2+12z-36=0 | | 2(x+3)-7=5(5-x)+7(x+1) | | m^2(9m+6)=8m | | 2000=1000 | | y=6/7x+4 | | -1y-5/-9y | | 3z(5z+6)=15z^2+18z-1 | | 9r^3+18r^2=72 | | -8x+y=53 | | 9x+5y=-29 | | -8x+y=25 | | 8x+2y=-22 | | 9y^2-45y/-9y | | log(4)*(5x-3)=1 | | 3/x-2=70 | | (3i/4-i) | | (31/4-i) |